Islam dan Tradisi Perspektif Al-Qur’an dan As-Sunnah - Madkan; Lusia Mumtahana (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2022)
Religion does not come to the archipelago in a space, previously it has rooted in the traditions of the ancestors. The author wants to know more about the Traditions that developed in Indonesia and look at them from the point of view of the Al-Quran and Sunnah. This research uses a qualitative method that is library research which uses books and other literature as the main object. A literature review serves to build concepts or theories that form the basis of studies in research. Primary sources are sources that provide data directly from first-hand or Islamic traditional books and journals. The results of this study are the Al-Quran and Sunnah are the main sources of Islamic law and the main thing is to be a guide to life for humans and as a guide for humans. Traditions that are born, whether in the form of thoughts, rules, or social order, as well as those with a material pattern, will not be separated from the soul of the Qur'an and Sunnah.